Study on Explosive Fracturing Mechanism of Qianjiang Shale Oil - Jing Luo; Yingtao Xu; Ruidi Tian; Fei Sun; Haitao Yu; Dong Xiang; Weichu Yu (Applied Sciences)
We employed the nonlinear finite element software ANSYS LS-DYNA 19.0 to develop a coupled dynamic-static load model for shale oil reservoirs in the Qianjiang Depression through theoretical analysis and numerical simulation and to investigate an oil extraction technology by improving oil yield while maintaining environmental sustainability of Qianjiang Depression. The effects of various loading conditions, including hole size and different oxygen balance of explosives, on oil recovery efficiency during reservoir rock blasting are extensively examined. Numerical simulations reveal that NTNMT explosions transfer more energy to the reservoir rock, compared to DEGDN and TNT. Specifically, when the charging radius is set to 6 cm, NTNMT yields optimal fracture expansion and coalescence, leading to improved economic benefits for shale oil extraction. Additionally, density functional theory (DFT) simulations were conducted to analyze the decomposition processes of different oxygen balance explosive molecules within the reservoir and assess their potential pollution. The results indicate that all the explosives can degrade reservoir rocks, but the explosion of positive oxygen balance, NTNMT, exhibits the highest degradability and lowest environmental impact.